(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
The only hope for a patient suffering from organ failure is transplantation from a healthy donor and advances in the medical field have enabled the use of several organs for transplant purposes. Harvesting / retrieval of organs from the Non Heart-Beating Donors (NHBDs) is the most common method for procuring organs like eyes, kidneys, liver, pancreas, intestines, lungs, heart, etc. However, of all these organs, kidneys are the most commonly transplanted organs as they are the ones that can be procured even from the living. Since a person can survive with a single kidney, people in the underdeveloped and developing countries are lured into selling them to a wealthy recipient, usually from the oil rich Middle-East Countries or the West. This has led to a newer concept in the tourism world- “Transplant Tourism”. Wealthy recipients come to preplanned destinations for the purpose of transplantation where organs, particularly kidneys, procured illegally from the poor are transplanted for huge profits. The donors, who are usually impoverished and illiterate, are robbed off both their organs and just due.